Born in 1919 : Fred Korematsu, Jackie Robinson - Knutson, Julie (Knutson, Julie. Parallel lives., 2020)
Examines the lives of Fred Korematsu and Jackie Robinson, both born in 1919, and tracking their unique experiences and how they responded to their struggles and worked to change the world for the better. Includes a timeline showing their lives in parallel, as well as a glossary.